Risk of Periodontal Disease in Patients with Osteopenia and Osteoporosis - kizi, Toshtemirova Mokhira Makhmud; G’ofurovich, Jurakulov Abbos (American Journal of Biomedicine and Pharmacy, 2024)
Based on a survey of 3150 patients over 3 years of operation of the office for the prevention and treatment of osteoporosis at a dental clinic, the risk of periodontal disease in patients with osteopenia and osteoporosis, average age 57.6 ± 17.3 years, was analyzed. A significant inverse correlation between bone mineral density and periodontal index has been established. Severe chronic periodontitis with osteoporosis is observed more often than with osteopenia and normal bone density. Its risk in patients with osteoporosis increases 5 times. The severity of periodontal damage in them is also determined by cardiovascular diseases, in most cases combined, including with type 2 diabetes mellitus.